Seroprevalence of SARS-CoV-2 immunoglobulin antibodies in Wuhan, China: part of the city-wide massive testing campaign. (February 2021) - Pan, Yunbao; Li, Xinran; Yang, Gui; Fan, Junli; Tang, Yueting; Hong, Xiaoyue; Guo, Shuang; Li, Jin; Yao, Dongai; Cheng, Zhenshun; Yuan, Yufeng; Li, Yirong; et al.
Abstract: Objectives: The outbreak of the 2019 coronavirus disease (COVID-19) pandemic in Wuhan, China, has subsided after being hard hit by the disease and subsequent city lockdown. Information on the number of people involved in Wuhan is still inadequate. This study aimed to describe the screening results of 61 437 community members in Wuchang District, Wuhan. Methods: In mid-May 2020, Wuhan launched a population-scale city-wide SARS-CoV-2 testing campaign, which aimed to perform nucleic acid and viral antibody testing for citizens in Wuhan. Here we show the screening results of cluster sampling of 61 437 residents in Wuchang District, Wuhan, China. Results: A total of 1470 (2.39%, 95% CI 2.27–2.52) individuals were detected positive for at least one antiviral antibody. Among the positive individuals, 324 (0.53%, 95% CI 0.47–0.59) and 1200 (1.95%, 95% CI 1.85–2.07) were positive for immunoglobulin IgM and IgG, respectively, and 54 (0.08%, 95% CI 0.07–0.12) were positive for both antibodies. The positive rate of female carriers of antibodies was higher than those of male counterparts (male-to-female ratio of 0.75), especially in elderly citizens (ratio of 0.18 in 90+ age subgroup), indicating a sexual discrepancy in seroprevalence. In addition, viral nucleic acid detection using real-time PCR had showed 8 (0.013%, 95% CI 0.006–0.026) asymptomatic virus carriers. Discussion: The seroprevalence of SARS-CoV-2 in Wuhan was low. Most Wuhan residents are still susceptible to this virus. Precautions, such as wearing mask, frequent hand hygiene and proper social distance, are necessary before an effective vaccine or antiviral treatments are available.